In situ study of the annealing process of a polyethylene cast film with a row-nucleated crystalline structure by SAXS. Issue 35 (18th March 2015) - Xu, R. J.; Chen, X. D.; Cai, Q.; Chen, C. B.; Lin, Y. F.; Lei, C. H.; Li, L. B.
Abstract : The secondary crystallization has more effect on polyethylene crystal thickening than melt recrystallization during the annealing process. Abstract : An in situ annealing process of a polyethylene cast film with a row-nucleated crystalline structure was followed using a SAXS setup equipped with a temperature-controlling unit. The annealing temperatures were set at 105 °C, 115 °C and 125 °C, respectively. It was found that after annealing for 7200 s, the long period, crystalline thickness, the real amorphous layer thickness and diffuse transition layer thickness were increased, whereas the linear crystallinity didn't show a pronounced change. Compared with those at 105 °C and 115 °C, annealing at 125 °C resulted in an apparent increase of the long period and crystalline thickness, as well as the crystalline thickening rate. During the initial annealing stage, the crystalline thickness was increased apparently. After annealing for 1800 s, the crystalline thickness versus annealing time curve showed a wave-like shape, due to the occurrence of melting and recrystallization behavior, which could not be observed during the early annealing stage. The initial crystalline thickness increase was mainly due to the crystallization of some tie chains in the amorphous region, as well as a small transformation of the diffuse transition layer into the crystalline region. The crystalline orientation degree based on the width of the SAXS patterns was improved apparently when the annealing temperature was around the maximum crystalline temperature. This work clarified the increase of crystalline thickness induced by annealing a polyethylene film with a row-nucleated crystalline structure.